Isolation and identification of a red pigment producer endophytic fungus Monascus sanguineus from Rehmannia glutinosa Libosch - HE Yatao; GAO Dandan; GAN Senning; SUN Ting; CAI Kuizheng; LIU Junlin (浙江大学学报. 农业与生命科学版, 2019)
Fungal pigments are the potential resources as a natural food colorant. An endophytic fungus RJL03, which is able to produce abundant soluble red pigments, was isolated from the medicinal plant Rehmannia glutinosa Libosch. For further research and utilization of this strain and its secondary metabolites, morphological and molecular characteristics of RJL03 were identified. For observing the colonial morphology, the strain was cultured on different substrates at 25℃ for seven days. The fungus was also observed through light microscope and scanning electron microscope. The colony of this fungus was white at first and turned red at later stage, villous, circular; the mycelium was composed of irregularly branched, septate; conidia had borne terminally on pedicels, single or 2-10 in chain, which was about (8.0-16.5) μm×(7.5-14.0) μm; the cleistothecia was globose, brown, arising terminally from the apex of short hyphae, whose diameter was 32-70 μm; the ascospore was ellipsoidal, smooth, colorless or red, which was about (6.0-7.5) μm×(4.0-5.0) μm. Sequence analysis showed that ITS and 18S of the strain had 100% and 93% similarities with Monascus sanguineus, respectively. In conclusion, morphological results and phylogenetic analysis provided great evidence that endophytic fungus RJL03 was M. sanguineus. This study first reported M. sanguineus isolates from Rehmannia glutinosa Libosch. in China. It is considered that M. sanguineus, unlike M. purpureus, should be an independent species.